A potential mechanism of the onset of acute eosinophilic pneumonia triggered by an anti‐PD‐1 immune checkpoint antibody in a lung cancer patient. Issue 1 (21st November 2018) - Jodai, Takayuki; Yoshida, Chieko; Sato, Ryo; Kakiuchi, Yosuke; Sato, Nahoko; Iyama, Shinji; Kimura, Tomoko; Saruwatari, Koichi; Saeki, Sho; Ichiyasu, Hidenori; Fujii, Kazuhiko; Tomita, Yusuke
Abstract: Introduction: The impact of immune checkpoint blockade on immunity in cancer patients is not completely elucidated due to the complexity of the immune network. Recent studies have revealed a significant role of programed cell death‐ligand 2 (PD‐L2) in negatively controlling the production of CD4+ T helper type 2 (Th2) cytokines and airway hypersensitiveness, suggesting hypo‐responsive Th2 cells via the PD‐1/PD‐L2 inhibitory pathway in lung could be reawaken by PD‐1 blockade therapy. Methods: We describe the first report of acute eosinophilic pneumonia (AEP), which is known as Th2‐associated pulmonary disease, triggered by nivolumab, an anti‐PD‐1 antibody, in an advanced non‐small cell lung cancer patient. Based on the current case report and literature, the present study proposes a potential mechanism of the onset of AEP as an immune‐related adverse event (irAE). Results: A 62‐year‐old man was diagnosed with lung adenocarcinoma and nivolumab was selected as the third‐line regimen. After three cycles of nivolumab treatment, chest computed tomography revealed pulmonary infiltrates in both lungs. The patient was diagnosed with AEP based on the diagnostic criteria for AEP. Nivolumab was suspended and the patient was started on oral prednisolone. His symptoms and radiological findings had rapidly improved. Conclusions: Given the increasing frequency of the use of anti‐PD‐1 antibodies, clinicians should be aware of the risk of AEP as a potential irAE. This study may improve our understanding of the pathophysiology underlying Th2‐associated irAEs and AEP. Abstract : In present study, we report that the first case of acute eosinophilic pneumonia (AEP) triggered by nivolumab, an anti‐PD‐1 antibody, in an advanced non‐small cell lung cancer patient. We propose a potential mechanism of the onset of AEP as an immune‐related adverse event (irAE).